Lila [compact disc, unabridged] - Robinson, Marilynne (Macmillan Audio, 2014)
Lila, homeless and alone, steps inside a small-town Iowa church and ignites a romance and a debate that will reshape her life. She becomes the wife of a minister, John Ames, and begins a new existence. Neglected as a toddler, Lila was rescued by Doll, a young drifter, and brought up by her in a hardscrabble childhood. When Lila arrives in Gilead, she struggles to reconcile their days of hardship with the gentle Christian worldview of her husband which paradoxically judges those she loves.